Service Learning in Interpreter Education : Strategies for Extending Student Involvement in the Deaf Community - Shaw, Sherry (Book collections on Project MUSE., 2013)
Institutions of higher learning around the nation have embraced the concept of student civic engagement as part of their curricula, a movement that has spurred administrators in various fields to initiate programs as part of their disciplines. In response, sign language interpreting educators are attempting to devise service-learning programs aimed at Deaf communities. Except for a smattering of journal articles, however, they have had no primary guide for fashioning these programs. This book serves as a remedy. The author begins by outlining how to extend student involvement beyond the field experience of an internship or practicum and suggests how to overcome student resistance to a course that seems atypical. She introduces the educational strategy behind service-learning, explaining it as a tool for re-centering the Deaf community in interpreter education. She then provides the framework for a service-learning course syllabus, including establishing Deaf community partnerships and how to conduct student assessments. The book concludes with first-person accounts from students and community members who recount their personal and professional experiences with service learning. With this thorough guide, interpreter education programs can develop stand-alone courses or modules within existing coursework.